Prosedur Perawatan Sekoci Guna Menunjang Keselamatan Jiwa Di Laut - Defilio Sundame, Defilio; Yosis Onasis; Santun Irawan (Politeknik Pelayaran Sulawesi Utara, 2022)
Lifeboats are one of the safety devices used to leave the ship in the event of an emergency which aims to save the lives of the ship's crew on board. Lifeboats must always be in a ready-to-use condition, so maintenance is required according to the SOLAS standard which discusses the standardization of safety equipment on board including lifeboats. solving problems regarding the obstacles in the implementation of lifeboat maintenance and efforts to overcome obstacles in the implementation of lifeboat maintenance. Before carrying out the maintenance of the lifeboat, there must be a maintenance plan, so that it can be seen which parts of the lifeboat require treatment first. In writing this scientific paper, the researcher uses qualitative methods. Observations, documentation and literature studies are carried out to collect relevant data. Data analysis is defined as an activity carried out to change the data resulting from a research into information that can later be used to draw a conclusion. Based on the results of the study, it can be seen that the researchers describe the results obtained during the research, namely the maintenance of lifeboats on the shipMT.MITRA KEMAKMURAN